Penegakan Hukum Tindak Pidana Kekerasan dalam Rumah Tangga (Studi Kasus di Polresta Yogyakarta Tahun 2011-2013) - M. Jamil (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2015)
This study discusses the law enforcement criminal acts of domestic violence,which is more specialized in Yogyakarta Police 2011 - 2013. The results show thatthe process of inquiry and investigations conducted by the Police Yogyakarta onumumya are in accordance with Law No. 23 of 2004 on the Elimination of DomesticViolence, Law No. 2 of 2002 on Police and other laws. There are some things thatneed to be improved as maximizing PKDRT socializing and working with agencies orinstitutions to minimize the occurrence of domestic violence. Factors that lead todomestic violence in the jurisdiction of Police of Yogyakarta that factors jealous, factorbecause it has a PIL / WIL (affair), economic factors, because of religious teachingsallow, the education factor is low, a factor for their early marriages, lack ofunderstanding of the religious affiliation , as well as the presence of a third party (theaffair)